Reinterpretation of Tarekat and the Teachings of Sufism According to Said Nursi - Cemal Sahin; Zaimul Asroor (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2021)
In this modern-contemporary era, Muslims are often faced with the question, â€œIs it necessary to follow the teachings of the tarekat? Didnâ€™t the tarekat (especially after al-Ghazali criticized the philosophical tradition) cause Muslims to decline and lose their critical power?â€ Moreover, some sufism teachings such as wahdatul wujud, wahdatus syuhud etc. Often considered as deviating from the pure teachings of Islam, especially by the Wahabi group. In order to answer some of these questions, the writer tries to present how Said Nursi responds in the interpretation of Risalah Nur. Nursi said that,